Naphthoquinone derivatives exert their antitrypanosomal activity via a multi-target mechanism. - Simone Pieretti; Jurgen R Haanstra; Muriel Mazet; Remo Perozzo; Christian Bergamini; Federica Prati; Romana Fato; Giorgio Lenaz; Giovanni Capranico; Reto Brun; Barbara M Bakker; Paul A M Michels; et al. (Public Library of Science (PLoS), 2013)
BACKGROUND AND METHODOLOGY: Recently, we reported on a new class of naphthoquinone derivatives showing a promising anti-trypanosomatid profile in cell-based experiments. The lead of this series (B6, 2-phenoxy-1,4-naphthoquinone) showed an ED(50) of 80 nM against Trypanosoma brucei rhodesiense, and a selectivity index of 74 with respect to mammalian cells. A multitarget profile for this compound is easily conceivable, because quinones, as natural products, serve plants as potent defense chemicals with an intrinsic multifunctional mechanism of action. To disclose such a multitarget profile of B6, we exploited a chemical proteomics approach. PRINCIPAL FINDINGS: A functionalized congener of B6 was immobilized on a solid matrix and used to isolate target proteins from Trypanosoma brucei lysates. Mass analysis delivered two enzymes, i.e. glycosomal glycerol kinase and glycosomal glyceraldehyde-3-phosphate dehydrogenase, as potential molecular targets for B6. Both enzymes were recombinantly expressed and purified, and used for chemical validation. Indeed, B6 was able to inhibit both enzymes with IC(50) values in the micromolar range. The multifunctional profile was further characterized in experiments using permeabilized Trypanosoma brucei cells and mitochondrial cell fractions. It turned out that B6 was also able to generate oxygen radicals, a mechanism that may additionally contribute to its observed potent trypanocidal activity. CONCLUSIONS AND SIGNIFICANCE: Overall, B6 showed a multitarget mechanism of action, which provides a molecular explanation of its promising anti-trypanosomatid activity. Furthermore, the forward chemical genetics approach here applied may be viable in the molecular characterization of novel multitarget ligands.